2018
DOI: 10.1029/2018gl079090
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Lower Harmonic Magnetosonic Waves Through Nonlinear Wave‐Wave Interactions

Abstract: Although magnetosonic waves in the Earth's magnetosphere have been well understood by the linear theory, low harmonic magnetosonic waves, which often lack of free energy, can be unusually present. By employing a 1‐D particle‐in‐cell simulation model, we have investigated the generation of those unusual lower harmonic magnetosonic waves in a plasma containing a proton ring distribution. In our simulation, the higher harmonic magnetosonic waves (from~9Ωh to ~12Ωh) are firstly excited due to the unstable proton r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…One discrepancy is the presence of a weak second harmonic in the simulation, which is not unstable according to the linear theory. The formation of the relatively weak second harmonics may be caused by the nonlinear wave‐wave coupling (Chen et al, ; Gao et al, ). Based on the diagnosis of wave properties and the comparison with the linear theory, it is safe to conclude that the excited fluctuating electromagnetic fields in our simulations are indeed magnetosonic wave mode generated by the proton ring distribution.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…One discrepancy is the presence of a weak second harmonic in the simulation, which is not unstable according to the linear theory. The formation of the relatively weak second harmonics may be caused by the nonlinear wave‐wave coupling (Chen et al, ; Gao et al, ). Based on the diagnosis of wave properties and the comparison with the linear theory, it is safe to conclude that the excited fluctuating electromagnetic fields in our simulations are indeed magnetosonic wave mode generated by the proton ring distribution.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The PIC simulation model is a powerful tool to investigate the plasma process via a self-consistent way (Sun et al 2016(Sun et al , 2017Lu et al 2016;Ke et al 2017;Gao et al 2018;Chen et al 2018). In this paper, a 1-D PIC simulation is used to study the expansion of hot electrons in a magnetic mirror field.…”
Section: Simulation Modelmentioning
confidence: 99%
“…The results of another 1-D PIC simulations by Gao et al (2018) showed that initial growth of EMWs, driven by an unstable proton ring distribution, occurred at harmonics in the range 9-12 Ω p . Later in the simulation, emissions at lower harmonics were observed.…”
Section: Introductionmentioning
confidence: 98%